Analysis Value of The Official Trailer of Film “The Santri” in Living Hadith Perspective - Kholidun Kholidun; Lilik Channa (Jurnal Living Hadis, 2022)
This study intends to observe moral values in the Official Trailer of the Film "The Santri". The type of this research is a qualitative descriptive study with the research subject, namely the Official Trailer of the Film "The Santri" produced by the Nahdlatul Ulama (PBNU) Board. Descriptive research is research that is obtained in the form of words, pictures from the official trailer of the film "The Santri" and not data in the form of numbers. Primary data collection procedures used using listening, taking notes, interviews, observation (field notes), and documentation. The research results that have been described, namely the Official Trailer of the film "The Santri" contain good moral values for all groups and all ages, including educational, cultural, moral values, strengthening personality, integrity, for the millennial generation in the perspective of Living Hadith. This film can be used as a reference and a means of moral education for children with the guidance of parents as well as for adolescents and can be used as a means of cultivating morals so that the positive values in the film can be digested by the children properly.